Double shear test on bonding mechanical properties of sprayed FRP and concrete substrate. (1st April 2019) - Yang, Zhao; Li, Jiajia
Abstract: To study the bonding mechanical properties of the interface between sprayed FRP and concrete substrate, seven double shear specimens were made to do the double shear tests. The failure mode, load and deformation, shear strength and deformation, distribution of strain and stress were studied. Furthermore, the influence of three main factors including fiber volume ratio, thickness of sprayed FRP and bonding length were analyzed in the paper as well. The results show that the thickness of sprayed FRP and bonding length have great influence on the bonding mechanical properties, while fiber volume ratio has little. The bonding interface that participate in bearing shear load can only develop to a certain length and then move from loading end to the other end with the development of debonding. The study can provide reference to the further research on sprayed FRP material used in concrete structure reinforcement.